2012
DOI: 10.1111/j.1365-2648.2012.05949.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding spasticity from patients’ perspectives over time

Abstract: Spasticity as experienced is complex, involving a wide range of unusual sensations sensitive to stressors in everyday life. Clinical evaluation of spasticity should include patient reports. Knowledge about patient word choice used to describe spasticity can enhance communication with healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…Previous studies have found that patients typically use words reflecting muscle tone and spasms to describe spasticity. [16] For this reason, although the survey was entitled ''Patients Living With Spasticity'', all questions were worded in the context of their ''muscle stiffness'' and/or ''muscle spasm''.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that patients typically use words reflecting muscle tone and spasms to describe spasticity. [16] For this reason, although the survey was entitled ''Patients Living With Spasticity'', all questions were worded in the context of their ''muscle stiffness'' and/or ''muscle spasm''.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this ignores the important aspect of sensory input in the experience of spasticity. Lance's [5] definition is therefore limiting and somewhat misleading [6]. Therefore, it is imperative that clinical practice incorporates the new 21st century definition to operationalize the management of spasticity.…”
Section: Pathophysiology Of Spasticitymentioning
confidence: 99%
“…Ethical clinical practices require clinicians to incorporate patients' understanding of this phenomenon in their plan of care. Bhimani et al's [6] original study reports on the patient understanding of spasticity and their results indicate that there is a discrepancy between patients and clinicians understanding of spasticity. Therefore, omitting patient reports from clinical decision making can have grave and serious consequences on their lives manifesting as side-effects of spasticity therapy, administration of invasive and inappropriate therapies, unnecessary pain, and suffering.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Although avoiding these triggers is often included in spasticity management for various neurological conditions, 12-14 the evidence to support their influence on spasticity is limited, and the existing literature has focused primarily on the population with spinal cord injury (SCI). [15][16][17][18][19][20] Our study, focusing on a population of people with stroke or MS living in the community, had the following objectives: (1) to describe the distribution (limb and side affected), extent (severity), and impact (effects on ADL) of spasticity; (2) to identify factors perceived to influence severity of spasticity; and (3) to determine whether there is an association between time since diagnosis and the perceived impact of spasticity on ADL.…”
Section: Ré Sumémentioning
confidence: 99%